A SOCIOCULTURAL APPROACH TO SCIENCE EDUCATION - Kenneth Tobin (Pontificia Universidad Javeriana, 2013)
I present a sociocultural approach to research and science education that incorporates a recursive relationship between transformation and theory, acknowledges the strengths of subjectivity, and regards difference as a resource for learning. The methodology incorporates hermeneutic-phenomenology, reflexive inquiry, and event-oriented inquiry. Research on emotions contextualizes methodologies for multidisciplinary and multi-level research. Finally, a new journal that was developed as a home for cultural studies of science education is described along with the processes used in manuscript review and publication.